Psychological Consequences of Social Isolation and its Link with Positive Psychological Functioning - Portela, Mayda Alejandra (2022)
Objective. Evaluate the psychological effects of social isolation (post-traumatic stress symptoms) associated with the global pandemic situation and the possible association with positive psychological functioning. Method. The design was a cross-sectional study with 440 participants between 18 and 65 years old (M = 35.25) selected through convenience sampling. Sociodemographic, coexistence and occupation data were collected. The information was collected online, between April and July 2020. A descriptive and comparative analysis of the variables was carried out. Results. A relationship between Social Isolation and Post Traumatic Stress Symptoms was observed. Positive psychological functioning was inversely correlated with social isolation and post-traumatic stress symptoms, which are more evident in the middle and older age ranges (36-50 and 51-65). Positive psychological functioning showed higher levels in the 51-65 age group and in participants from the interior of the country. Symptoms of anxiety and depression were greater in young people (18-25 years old), women, city residents, and people living with their parents. These data can inform treatment strategies that attempt to reduce the psychological symptoms of COVID-19 isolation, based on psychological resources.